Seismic site characterization and development of SPT(N) to shear wave velocity correlation of Noida city - Pankaj Kundu; Devagya Raman; Anindya Pain; Josodhir Das; Ravi Sundaram; Sorabh Gupta (Scientific Reports)
Abstract Noida, situated in proximity to major tectonic structures within a seismically active region, is susceptible to earthquake hazards. The destruction caused by an earthquake is influenced by the soil characteristics at a site, which play a significant role in amplifying ground shaking. To mitigate these devastating effects, it is essential for design practices to account for local site effects in seismic site characterization studies. Seismic site characterization using shear wave velocity ( $$V_{S}$$ ) is typically performed through the Seismic cross-hole test (CHST), which is challenging to implement in densely populated areas. However, the Standard penetration test (SPT–N), a method widely used by civil engineers, can be leveraged to estimate $$V_{S}$$ in such areas by developing correlations between $$V_{S}$$ and SPT–N values. The present study aims to develop empirical correlations between standard penetration test (SPT-N) values and shear wave velocities ( $$V_{S}$$ ) derived from seismic cross-hole tests and standard penetration tests. This study is significant because no prior seismic site characterization studies exist for Noida. From a total set of 117 boreholes, Geotechnical data from 26 boreholes and geophysical data from 14 seismic cross-hole tests (CHST) spread across Noida are utilized to establish a reliable SPT- $$V_{S}$$ correlation using non-linear regression analysis. The proposed correlations were benchmarked against global standards and validated with preexisting global and local correlations. Also, the proposed correlation is validated by several graphical approaches to demonstrate its error range. The developed correlation is further used to estimate the shear wave velocity ( $$V_{S}$$ ) profile for all the 117 boreholes. The findings leads to the development of a comprehensive seismic site classification map for Noida city, which categorizes subsoil into various classes based on average $$V_{S}$$ ( $$V_{S30}$$ ) and average SPT-N ( $$N_{30}$$ ) values of the top 30 m of the subsurface, based on NEHRP (National Earthquake Hazard Reduction Program) site classification scheme (BSSC (2001). NEHRP recommended provisions for seismic regulations for new buildings and other structures (FEMA 368). Building Seismic Safety Council for the Federal Emergency Management Agency, Washington, DC, USA.). The city is located in the Indo-Gangetic plain (IGP) which is very close to seismically active Himalayas. Considering those facts, this seismic site classification is essential for constructing earthquake-resistant structures and for regional seismic microzonation efforts. The study is crucial for Noida’s urban planning and safety regulations, addressing the city’s vulnerability to seismic activities by providing detailed insights into its subsurface properties.